The artist between court and city: (1300-1600) = L’ artiste entre la cour et la ville - Eichberger, Dagmar; Lorentz, Philippe; Tacke, Andreas (Michael Imhof Verlag, 2017)
Sophisticated Courtier or skilled Artisan? Re-assessing modern notions of the artist in the late Middle Ages and the Early Modern Period / Dagmar Eichberger and Philippe Lorentz -- Artistes et maîtres d'œuvre au service des conseillers royaux dans la France des années 1300 / Sabine Berger -- Des artistes à la cour. Le cas d'une petite cour aux confins septentrionaux du Royaume - le Hainaut des Avesnes et des Bavière / Ludovic Nys -- Peintre et valet de chambre à la cour de France aux XIVe et XVe siècles - titre honorifique ou poste budgétaire? / Philippe Lorentz -- Just Reward? Reflections on (and new Evidence for) Jean Bourdichon's Administrative Role at Court / Nicholas Herman -- Status 'Malerfürst' - Konstrukt oder soziales Phänomen? / Doris H. Lehmann -- Les artistes du bâtiment installés à la cour du duc de Berry - Un privilège? / Thomas Rapin -- Batir pour la cour, bâtir pour la ville. Les architectes-fonctionnaires à Bruxelles (XIVe-XVIIe siècles) / Boris Horemans and Bram Vannieuwenhuyze -- The "Emperor's Artists" between Court and the City in the Sixteenth-Century Low Countries / Krista De Jonge -- Up at the Castle and Down Town Prague. The position of the Baumeister at the Habsburg Courts in Prague and Vienna in the middle of Sixteenth Century / Madelon Simons -- Zu Diensten der Stadt und des Hofes - Georg Pencz (um 1500-1550). Ein "ehrbarer Diener" der Reichsstadt Nürnberg / Katrin Dyballa -- Entre consuls et rois. Jean Perréal et les peintres lyonnais, Tania Lévy -- A guild's eye view on art. Artists and the corporate world in Antwerp (ca. 1550-1600) / Natasja Peeters -- Süddeutsche Stadtmaler im 16. und 17. Jahrhundert - Versuch einer Verortung / Danica Brenner -- Urban Craftsmen and the Courts in Sixteenth-Century Germany / Andrew Morrall -- Les brodeurs de cour et la corporation parisienne au XVIe siècle / Astrid Castres -- Maître de corporation, artiste à la cour, émissaire de Monseigneur l'évêque - les divers emplois de Paul Nitsch (1548-1592), orfèvre à Wrocław / Aleksandra Szewczyk -- Netherlandish artists and craftsmen at the court of Julius, Duke of Brunswick-Lüneburg / Aleksandra Lipińska -- Lazy Foreigners and Indignant Locals - Influence and Rivalry in Bavarian Court Patronage / Susan Maxwell -- Stadt und Hof im frühen 16. Jahrhundert. Zwei Szenarien der Kunstproduktion im Herzogtum Mecklenburg / Julia Trinkert -- Wenzel Jamnitzer - Famous yet free? / Jeffrey Chipps Smith -- Ein städtischer Hofkünstler - Christoph Schwarz / Sandra-Kristin Diefenthaler -- Ars longa, vita brevis - Tizians Geschäfte mit Holz und Getreide / Heiner Borggrefe -- Hofmaler und Zunftmaler. Künstlerschicksale aus dem 16. und 17. Jahrhundert im deutschen Sprachraum / Ursula Timann
Seite 9: "This volume derives from international conference "Civic Artists and Court Artists (1300-1600). Case studies and conceptual ideas about the status, tasks and the working conditions of artists and artisans" which took place at "INHA-Institut national d'histoire de l'art" in Paris 19-21 June, 2014."
Keywords: Konferenzschrift -- INHA - Institut national d'histoire de l'art -- 19.06.2014-21.06.2014 -- Paris; Geschichte 1300-1600; Künstler; Prestige; Soziale Stellung; Höfische Kunst; Hof; Stadt